The Cambridge illustrated history of ancient Greece (Cambridge University Press, 1998)
Sumptuously illustrated in color and packed with information, The Cambridge Illustrated History of Ancient Greece is now available for the first time in paperback. Offering fresh interpretations of classical Greek culture, the book devotes as much attention to social, economic and intellectual aspects as to politics and war. Paul Cartledge and his team of contributors ask what it was like for an ordinary person to partake in "the glory that was Greece." They examine the influences of the environment and economy; the experience of workers, soldiers, slaves, peasants and women; and the roles of myth and religion, art and culture, and science and education. This is a cultural history from the bottom up, which lays bare the far-reaching linguistic, literary, artistic and political legacy of ancient Greece, and seeks justification for Shelley's claim that "we are all Greeks." Paul Cartledge is Professor in Greek History in the Faculty of Classics at the University of Cambridge and is Fellow and Director of Studies in Classics at Clare College, Cambridge.